2004
DOI: 10.1038/sj.ejcn.1601926
|View full text |Cite
|
Sign up to set email alerts
|

Childhood stunting in Northeast Brazil: the role of Schistosoma mansoni infection and inadequate dietary intake

Abstract: This study was supported by the Thrasher Foundation. Sandra Maria Conceição Pinheiro is a National Council on Technological Development Scholarship Awardee (CNPq), #302228/81-0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
3
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 26 publications
2
47
3
4
Order By: Relevance
“…Though both stunting and wasting were prevalent in our study, we did not find the associations with schistosomiasis that other investigators have shown. [50][51][52] Our inability to reproduce the association is likely caused by residual confounding from unmeasured variables. The overwhelming support from other studies argues that anthropometry should remain in the toolkit for morbidity assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Though both stunting and wasting were prevalent in our study, we did not find the associations with schistosomiasis that other investigators have shown. [50][51][52] Our inability to reproduce the association is likely caused by residual confounding from unmeasured variables. The overwhelming support from other studies argues that anthropometry should remain in the toolkit for morbidity assessments.…”
Section: Discussionmentioning
confidence: 99%
“…[15,36] and intervention studies that showed improved growth performance after schoolchildren were treated with anthelminthic drugs [37][38][39][40]. Intestinal helminth infections could affect linear growth and nutritional status through several mechanisms including decline in food intake [39,41]; nutrient wastage from blood loss, malabsorption and diarrheal episodes [41,42]; and suppression of hormones required for bone growth like the growth hormone (GH) and insulin-like growth factor-1 (IGF-1) [43]. The WHO recommends regular school- based deworming programs with a target to cover at least 75% of school-aged children at risk by the year 2020 [44].…”
Section: Discussionmentioning
confidence: 99%
“…These concerns, together with a need to better understand a number of fundamental clinical and epidemiological aspects of human helminth infections as well as their interactions with geographically overlapping coinfections (e.g., malaria and HIV/AIDS) have created an urgency for stepped up clinical research activities as they relate to largescale helminth control. Such activities have focused around three major areas: first, a reexamination of the health impact of human helminthic infections, with particular interest in the effects of mono- and polyparasitism on childhood growth and development as well as their effects on pregnancy and birth outcomes (63,(136)(137)(138)(139)(140); second, large-scale monitoring and evaluation of MDA and integrated control, along with operational research with goals to improve the access of populations to anthelminthic drugs and to monitor for possible drug resistance (141)(142)(143)(144)(145); and third, the development of new tools to control helminth infections, that is, drugs, diagnostics, and vaccines (19,146).…”
Section: Global Control Of Helminthiases and Clinical Research Imperamentioning
confidence: 99%